Onrechtmatige Overheidsdaad: Menyoal Penerapan Regulasi dalam Praktik Penyelesaiannya di Peradilan Tata Usaha Negara Indonesia - Risandy, Diny Arista; Saibih, Junaedi Saibih (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum, 2024)
The existence of Supreme Court Regulation Number 2 of 2019 as a guideline governing the settlement of lawsuit against the law by authorities (Onrechtmatige Overheidsdaad/OOD) cases in the State Administrative Court has not been consistently implemented. This research, which uses normative legal research methods, discusses the fundamental problem related to the settlement of OOD cases after the issuance of the Regulation. The main problem is the dualism or inconsistency of judicial bodies authorized to examine, hear, and decide OOD cases. Another problem is the time limit for filing an OOD lawsuit with the court, which is considered unimplementable if it is filed no later than 90 (ninety) days from the time the government action is taken by taking into account the administrative efforts that need to be taken first by the party who feels aggrieved by the government. Some of these problems need to be addressed, among others, by reforming regulations and/or policies related to the settlement of OOD cases, which specifically focus on strengthening the State Administrative Court regime in holding the absolute authority to handle OOD cases as an override of the residual rechtspraak approach and reformulation of the provisions regarding the time period for filing an OOD lawsuit